Peran Pemerintah Kota Surabaya dalam Kebijakan Pemberdayaan Anak Disabilitas di Kota Surabaya - Putri, Abigail Maharani; Widuri, Ocha Aulia; Aliefia, Vony; Rohim, Ahmad Bagus; Saputri, Eka; Muljanto, Muhammad Agus (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Disability empowerment is one form of government effort in the welfare of people who have physical and mental limitations. The Surabaya City Government has currently made efforts to empower disabilities by providing formal and non-formal guidance activities. This is implemented by the development of Kampung Anak Negeri and Rumah Anak Prestasi under the auspices of the Surabaya City Social Service. This research uses descriptive qualitative methods with data collection techniques through observation, literature study, and in-depth interviews. The results obtained based on Gede Diva's theory are in line with the results of the research conducted, namely (1) Facilitator, as evidenced by providing several facilities such as providing assistance such as subsidies for goods, services or capital, providing training tailored to the needs of the target community of the program. (2) Regulator, as evidenced by the government to RAP and KANRI making regulations or rules and regulations related to the implementation of the disability empowerment program. (3) Catalyst, the government conducts technical guidance in carrying out empowerment before going to the field.